(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research seeks to propose global warming lists and audit them in accordance with the International Assurance Engagement Standard 3410 to reduce the effects of climate change. Preparing a proposed audit program for global warming lists contributes to the auditor verifying the extent of commitment to reducing greenhouse gas emissions by the concerned parties to reduce the effects of climate change. Climate, and the research community was represented in all sectors of the Iraqi environment for the years (2017-2020) (according to the availability of data). The two researchers relied on research tools in collecting data, which were the laws, regulations and instructions that are related to the subject of the research, Iraqi and Arab periodicals. And foreign books, Arab and foreign books, Iraqi, Arab and foreign letters and dissertations, the international network, direct interviews with some officials in the concerned authorities, reports of the competent supervisory authorities, field visits. The inductive approach was relied upon in dealing with the theoretical framework of the research, and the descriptive analytical approach in the practical side of the research. The two researchers reached a set of conclusions, most notably the absence of an audit program for global warming lists in accordance with Standard 3410 to reduce the effects of climate change. The most prominent recommendations were the researchers concluded that it is necessary to adopt the proposed audit program for global warming lists.